Mobility Practices, Attitudes and Perceptions of Nurses, Doctors and Physiotherapists Regarding Early Mobilisation of Critically Ill Patients in Intensive Care Units in Namibia. A Retrospective Record Review and Cross sectional Survey - Francis, Savarna Olivia (Division of Physiotherapy, 2022)
Background: The main focus of care in intensive care units (ICU) has historically been on preventing mortality. With advancing knowledge and technology, more patients now survive their ICU stay. Therefore, critical care priorities have recently shifted to preventing critical illness related morbidities, including ICU-acquired weakness (ICUAW) and delirium, in order to optimise functional, psychosocial, cognitive, and quality of life outcomes for survivors of critical illness and their families. Early mobilisation and ICU-based rehabilitation are recommended interventions to achieve these clinical objectives. There are no published studies describing early mobilisation practice in Namibia. Aims: This study aimed to describe the profile of patients admitted to two private intensive care units in Windhoek, Namibia, and to describe practices, attitudes and perceptions of nurses, doctors, and physiotherapists regarding early mobilisation of critically ill patients in those ICUs. Methodology: A retrospective, descriptive record review was conducted to describe the ICU patient profile and documented mobility practice. Charts of 870 patients admitted between 01 January 2016 and 31 December 2016 to two private Windhoek ICUs were included in the record review. A descriptive, cross-sectional, self-administered survey was used to assess knowledge of ICUAW and early mobilisation, reported mobility practice, personal views on early mobilisation, perceived contraindications/precautions to early mobility, the perceived barriers to the provision of early mobility, perceived permissible activity levels based on patient physiological status, and sedation practices. A total 39 nurses, doctors, and physiotherapists were included in the survey. Results: Record Review: 538 (61.8%) patients were male. Mean age was 56 (SD 14.9, range 18-90) years. Most admissions were elective (n=577; 66.3%). Coronary angiogram (n=179; 20.6%), cardiac conditions (n=113; 13%) and cardiac surgery (n=90; 10.3%) were the main admission diagnoses. Most patients (n=697; 80.1%) did not receive mechanical ventilation; average length of stay in ICU was 3.41 (1-37) days, and duration of mechanical ventilation was 0.7 (0-20) days. The mortality rate was 5.2%. Three hundred and fifty-two (40.5%) patients received physiotherapy treatment, with the majority (n=271; 78.6%) being mobilised once daily. Most patients (n=253; 73.3%) who were mobilised were done so within 48 hours of ICU admission. Physiotherapy techniques used were manual chest physiotherapy, mobilisation to a chair, and active range of motion exercises. Five (1.4%) patients experienced adverse events during physiotherapy treatment (change in systolic blood pressure to 200mmHg during treatment). Delirium was not assessed or monitored in any included patient. Survey: The overall response rate was 24.1% (n=42). Clinician group response rates were physiotherapists 10.2% (n=13); nurses 65.6% (n=21); and doctors 55.6% (n=5). Most participants underestimated the incidence of ICUAW (n=17; 44.7%) and reported unfamiliarity with the literature on early mobilisation (n=19; 51.4%). Twenty-five (38.5%) of sixty-five total physiotherapist responses reported they would mobilise patients once daily, while thirty-one (47.7%) responses reported they would mobilise patients twice daily. Twenty-seven (41.5%) physiotherapist responses reported they spend 16-30 minutes mobilising a patient. The mobilisation team described consisted mainly of physiotherapists, nurses, and porters. Routinely used physiotherapy techniques included manual chest physiotherapy, bed mobility, pre-gait activities and strengthening exercises. Providers reported conservativism in permissible patient activity levels, especially in ventilated patients. The most commonly reported barriers to early mobilisation were requiring a doctor's referral for mobilisation, medical instability, excessive sedation, safety concerns, inadequate training, and lack of communication. Conclusion: Patients were admitted electively, mainly post-cardiac surgery or for cardiac-related diagnoses. Delirium is not being standardly monitored in ICU. This could contribute significantly to poor patient outcomes. Quality improvement programmes to implement and optimise delirium monitoring and prevention in Namibian ICUs are recommended. Physiotherapists routinely use manual chest techniques, bed mobility, pre-gait activity, and strengthening exercises in ICU. Survey participants underestimated the likely incidence of ICUAW and lacked sufficient knowledge and training on early mobilisation. Many barriers to early mobilisation were identified in this study, which should be addressed through implementing quality improvement programmes to direct and improve ICU mobility practice. Future point-prevalence studies are recommended with larger sample sizes from both the private and public sectors to increase the generalisability of results.